2022
DOI: 10.1007/s10461-022-03789-0
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Retention in HIV Care, and Access to Ancillary Services for Young Black Men Living with HIV in Chicago

Abstract: This study conducted 28 semi-structured, in-depth interviews with Young Black Men who have Sex with Men in Chicago to investigate the impact of COVID-19 on their HIV care and ancillary service access. The qualitative analysis identified both negative and positive effects. The negative effects included: (l) mixed disruptions in linkage to and receipt of HIV care and ancillary services, and (2) heightened concerns about police and racial tensions in Chicago following the murder of George Floyd, contributing to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Improvement in linkage to HIV medical care, particularly during the COVID-19 period, was unexpected but may in part be due to innovations in service delivery. For example, a study with young Black MSM in Chicago showed continuing HIV care and ancillary service during COVID-19 through expanded use of telemedicine, which often delivered medications to patients' homes and eliminated transportation challenges 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement in linkage to HIV medical care, particularly during the COVID-19 period, was unexpected but may in part be due to innovations in service delivery. For example, a study with young Black MSM in Chicago showed continuing HIV care and ancillary service during COVID-19 through expanded use of telemedicine, which often delivered medications to patients' homes and eliminated transportation challenges 29 …”
Section: Discussionmentioning
confidence: 99%
“…For example, a study with young Black MSM in Chicago showed continuing HIV care and ancillary service during COVID-19 through expanded use of telemedicine, which often delivered medications to patients' homes and eliminated transportation challenges. 29 Our analysis consists of 3 limitations. First, these results are based on CDC-funded HIV testing data from health departments and CBOs and as such are not generalizable to linkage to HIV medical care from non-CDC-funded HIV testing in the United States.…”
Section: Discussionmentioning
confidence: 99%